Clinical Characteristics of Children with Febrile Seizure - Shrestha, D; Dhakal, A K; Shakya, H; Shakya, A; Shah, S C; Mehata, S (Journal of Nepal Health Research Council, 2015)
Background: Febrile seizure is common in children below five years of age. This study was conducted to evaluate the clinical profile of children presenting with febrile seizure in a teaching hospital.Methods: This was a descriptive retrospective study among children presenting with febrile seizure in a teaching hospital from July 2009 to June 2013. Children between six months to six years were included in the study while patients with prior episodes of afebrile seizures, abnormal neurodevelopment and not meeting the age criteria were excluded. Patientâ€™s demographic and clinical data were collected from the in-patients records and analyzed.Results: This study included 103 children with febrile seizure. Out of which 67% were male. Simple febrile seizureand complex febrile seizure were observed in 76.7% and 23.3% of patients respectively. Majority of children (71.8%)had generalized tonic clonic seizure followed by tonic seizures. Most of children (72.8%) who developed first episodeof seizure were below 24 months of age with the mean age of 20.7 (Â±12.1) months. Overall 33% of patients developed recurrence of febrile seizure and first episode of febrile seizure at age one year or below was associated with the seizure recurrence. Upper respiratory tract infections were the commonest cause of fever in these children.Conclusions: Febrile seizure was observed predominantly in children below age of two years and simple febrile seizure was the commonest variety. Recurrence of febrile seizure was common and significantly associated with the first episode of febrile seizure at the age of one year or below.Keywords: Complex febrile seizure; febrile seizure; recurrence; simple febrile seizure.